The Role of Self-Efficacy on Student Academic Procrastination in Completing Thesis: Literature Review - Mardiana, Nova (Universitas Malahayati, 2023)
ABSTRACT Academic procrastination is an act which deliberately delays the completion of academic assignments. One example is the delay in completing the thesis. Academic procrastination is influenced by internal and external factors. External factors are influenced by several things, namely self-regulation, self-efficacy, self-criticism, motivation and self-control. Self-efficacy is the belief that one can carry out activities or take the necessary actions to achieve certain results. To review the literature related to the relationship between self-efficacy and student academic procrastination in completing thesis. Article searches were carried out using the Scholar electronic database according to predetermined criteria. The combined keywords in the article search are in Indonesian, namely academic procrastination, self-efficacy and thesis then in English, academic procrastination, self-efficacy and thesis. The 10 research articles reviewed concluded that self-efficacy plays an effective role in reducing student academic procrastination in completing thesis. This literature review shows that there is a relationship between self-efficacy and delay in final student academic assignments. Keywords: Academic procrastination, self-efficacy, Thesis